Preventive care in inflammatory bowel disease - Harmandar, Ferda; Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Harmandar F, Çekin AH. Preventive care in inflammatory bowel disease. Turk J Gastroenterol 2017; 28: 307-10.